Virtual Pesantren Management in Indonesia: In Knowing Locality, Nationality, and Globality - Mukhibat, Mukhibat (IAIN Samarinda, 2020)
Virtual Pesantren is a new model of Islamic boarding school with no real form and place but having a similar function as a pesantren as a tafaqquh fi al addin institution. The characteristic of this pesantren is on its material development which is adjusted to the virtual students' needs with the use of appropriate language and relevant content so that it is easily understood. The problem occurs when the virtual pesantren raises an issue of the extreme purification practice that questions the authenticity of religion. This has led to a decline in the pesantren's historical vision – Islam and Indonesian (indigenous). The analysis of this study is descriptive qualitative. The report is presented in the form of a comprehensive and objective narrative based on data that has been classified and verified beforehand. Given these findings, pesantren is fundamentally built based on vision of pesantren which is tasamuh, tawassuth, and tawazun. Pesantren must be able to create a continuity and change in bonding between the values of locality, nationality, and globality as the basis of pesantren development.